2015
DOI: 10.3390/challe6010003
|View full text |Cite
|
Sign up to set email alerts
|

Retrofitting Precincts for Heatwave Resilience: Challenges and Barriers in Australian Context

Abstract: Abstract:As the frequency and intensity of heatwaves are growing in Australia, strategies to combat heat are becoming more vital. Cities are exposed to urban heat islands (UHIs) due to excess urbanisation. In this study, a definition of urban heatwave (UHW) is conceptualised to investigate the combined impacts of heatwaves and UHIs. To quantify the negative impacts of UHW, indicators-such as excess morbidity, electricity and water consumption-are considered. The intensity of UHWs is calculated using the unit o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 53 publications
(75 reference statements)
0
4
0
Order By: Relevance
“…With an estimate of 68% of the world population living in urban areas by 2050 and heatwaves posing a serious threat for the urban population, studies have investigated mitigating measures to adapt the built environment, making them more resilient to heatwaves [70,71,72,73]. A cool retrofitting toolkit proposed by Hatvani-Kovacs and Boland [71] to remodel existing precincts could make them more energy efficient and affordable, while Bennetts et al [70] proposed a combination of behavior modification and cooling refuges to increase thermal comfort and shielding penetration of heat. Both studies have concluded that there are means to reduce the impact of heatwaves without resorting to excessive energy consumption or high costs [70,71].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With an estimate of 68% of the world population living in urban areas by 2050 and heatwaves posing a serious threat for the urban population, studies have investigated mitigating measures to adapt the built environment, making them more resilient to heatwaves [70,71,72,73]. A cool retrofitting toolkit proposed by Hatvani-Kovacs and Boland [71] to remodel existing precincts could make them more energy efficient and affordable, while Bennetts et al [70] proposed a combination of behavior modification and cooling refuges to increase thermal comfort and shielding penetration of heat. Both studies have concluded that there are means to reduce the impact of heatwaves without resorting to excessive energy consumption or high costs [70,71].…”
Section: Discussionmentioning
confidence: 99%
“…A cool retrofitting toolkit proposed by Hatvani-Kovacs and Boland [71] to remodel existing precincts could make them more energy efficient and affordable, while Bennetts et al [70] proposed a combination of behavior modification and cooling refuges to increase thermal comfort and shielding penetration of heat. Both studies have concluded that there are means to reduce the impact of heatwaves without resorting to excessive energy consumption or high costs [70,71]. Those strategies present alternatives to current practices that policy makers could implement to mitigate the impacts of future heatwaves that are sustainable and equitable for older populations and do not further exacerbate greenhouse gas emissions.…”
Section: Discussionmentioning
confidence: 99%
“…The urban canyon effect, engendered by densely constructed and tall buildings, particularly during summer periods, impedes natural air circulation. Additionally, the presence of spaces that absorb and retain heat throughout both day and night exacerbate the adverse effects of rising temperatures (Oke, 1973;Hatvani-Kovacs & Boland, 2015). The concept of urban heat encompasses the cumulative impact of the urban heat island and heatwaves (Wang et al, 2022).…”
Section: Urban and Rural Vulnerability To Heatwavesmentioning
confidence: 99%
“…Although the Urban Heat Island (UHI) effect takes significant attention in studies examining the temperature-related impacts of climate change within urban areas (Hatvani-Kovacs & Boland, 2015), it is essential to acknowledge that rural areas are equally susceptible to climate change. While discussions regarding the impact of temperature rise on urban areas commonly assert that urban locales are more vulnerable than their rural counterparts due to inherent structural characteristics (De Sherbinin et al, 2007;Mora et al, 2017), it is noteworthy that divergent perspectives exist within the literature.…”
Section: Urban and Rural Vulnerability To Heatwavesmentioning
confidence: 99%